التحول نحو أساس الإستحقاق المحاسبي لتعزيز المساءلة وإدارة الموجودات الثابتة للقطاع العام في العراق (Journal of Accounting and Financial Studies ( JAFS ), 2020)
The research aims to present and discuss the accounting bases adopted in accounting for fixed assets in the public sector with an emphasis on its importance in the area of ​​accountability and fixed assets management , based on a realistic problem associated with the use of cash basis accounting in the public sector in Iraq, which are difficult  to provide accounting information useful for many users , including the same units and regulatory departments for the purposes of accountability and management of those assets. Search tool has been the organization questionnaire, its results show the importance of financial reporting for provide accounting information about fixed assets relate to the units of the public sector in Iraq for the purposes of accountability, management and development, and that the cash basis currently applied in those units does not provide such accounting information, so it is necessary to leave cash basis and the transition to the adoption of the accrual basis of accounting.